Pengaruh Kepemimpinan Transformasional Kepala Sekolah dan Profesionalisme Guru terhadap Mutu Pendidikan SMA Negeri se-Kabupaten Dharmasraya - Aulia Rahmawati; Asmendri Asmendri; David David (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
The main problem in this study is the lack of empirical knowledge of the influence of principals' transformational leadership and teacher professionalism on the quality of education in public senior high schools in Dharmasraya Regency. This study aims to analyze the positive and significant influence of principals' transformational leadership on educational quality. This study used a quantitative approach with an ex post facto design. The study was conducted in public senior high schools throughout Dharmasraya Regency. The study population consisted of 320 teachers. The sample size was determined using the Slovin formula, resulting in a sample of 178 teachers selected through stratified random sampling based on position. The research instrument was developed based on theoretical studies, then tested for construct validity using Confirmatory Factor Analysis (CFA) and for reliability using Cronbach's Alpha coefficient. The research instrument was declared valid and reliable, making it suitable for use as a data collection tool. Data collection was conducted through a closed-ended questionnaire. Data were analyzed using simple regression analysis and multiple regression analysis after meeting the analysis prerequisites. The results indicate a significant influence of principals' transformational leadership on educational quality in public senior high schools throughout Dharmasraya Regency. This is indicated by a significance value of